The forecasting of the number of passengers transported internationally by air in the United States for 2021 in terms of economic security - Sowa Bogdan; Tomaszewski Jarosław (2021)
The article presents a research problem that focuses on the forecasting of the number of passengers transported internationally by air in the United States - in terms of the impact of the COVID-19 pandemic and the maintenance of economic security. The research began with an analysis of the literature on issues such as transport, forecasting and economic security. Then, an analysis and evaluation of the time series of the number of passengers transported internationally by air in the United States from 1 January 2019 to 2 May 2021 were conducted. The obtained evaluation allowed for the selection of the forecasting method for the considered retrospective data. The forecast for the period from 3 May to 31 December 2021 was subjected to a comparative analysis with the same type of data from the same time period from 2019. The obtained evaluation allowed to achieve the goal set in the study. The forecast of the number of passengers travelling internationally by air in the United States for 2021 from 3 May to 31 December is 374 656 674 passengers.